TANGGUNG JAWAB NOTARIS TERHADAP PERALIHAN HAK ATAS TANAH MILIK ORANG TUA YANG BERASAL DARI WARISAN TANPA PERSETUJUAN AHLI WARIS (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 948 K/PDT/2017) - ALEXANDER LEOMANDRA (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Muhd Yamin, SH, MS, CN2. Notaris Dr. Suprayitno, SH, MKn3. Dr. T. Keizerina Devi A, SH, CN, MHum A notary is obliged to act honestly, conscientiously, independently, and impartially; and to protect the interests of related parties in taking a legal action before him pursuant to Article 16 paragraph 1 letter a of the Law No. 2/2014. This is a normative juridical research. It uses secondary data to answer the research problems. Library research is done to obtain the secondary data. The results of the research conclude that legalization of parents’ land in the sale and purchase agreement can be done by firstly ensuring if the land is the parents’ personal or joined property which is included into inheritance for their heirs. The sale and purchase of parents’ house to one of their children is valid and the notary has to know whether or not the house or land is included into inheritance.Keywords: Responsibility, Notary, Land Title Transfer, Parents, Inheritance, Heir’s Approval.